The contribution of the fruit and vegetables on the menu in the association between food insecurity and diabetes incidence among Indonesian adults - Emyr Reisha Isaura; Yang-Ching Chen; Shwu-Huey Yang (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose: The link from food insecurity to chronic diseases is well-known. However, the contribution of the number of days eaten fruits and vegetables consumption in the association between food insecurity and the incidence of diabetes among Indonesian adults is rather vague. Methods: This study was obtained data from 3955 participants of the Indonesia Family Life Survey (IFLS) in 2007 and 2014. The food insecurity measurement was using a World Food Programme (WFP) concept using food frequency questionnaire on a food consumption score analysis. A generalized estimating equation (GEE) test were used to test the hypotheses model while accounting for the health behaviors and sociodemographic characteristics in this study. Results: The GEE test was confirmed the negative association between food insecurity and diabetes in the adjusted and unadjusted model (p = 0.005 – < 0.001). The number of days eaten vegetables consumption was statistically negative associated with diabetes in both model (p = 0.006 – < 0.001). The number of days eaten fruits consumption was negatively associated with diabetes but not statistically significant in both models. The contribution of number of days eaten fruit and vegetables was related to the ability and/or knowledge of individuals to choose their meals, especially for people with diabetes. Conclusion: Food insecurity is negatively associated with diabetes, with the contribution of less number of days eaten vegetables consumption. Strategies to improve the prevention of diabetes among adults may need an enrichment of fruit and a vegetable tailored-meal on the menu of the restaurant or food court or canteen together with the enrichment of nutrition education, into account.